Perceptions of Social Isolation During Institutional Rehabilitation among Adults with Intellectual Disabilities: Recommendations for Integration - Agrippa Mabvira 1 1 Department of Social Work (E-Journal of Humanities, Arts and Social Sciences)
It is quite commendable that over the past 50 years, there has been a massive move towards deinstitutionalisation globally. However, this paper concurs with the view that despite the move towards deinstitutionalisation, people with intellectual disabilities sometimes feel the effects of institutionalisation in special schools which offer boarding arrangements and in day centres and workshops catering for large groups of adult persons. This qualitative study involved 12 participants with moderate intellectual disabilities and three key informants at an adult centre that caters for adults with intellectual disability in Zimbabwe. The study revealed that individuals with intellectual disabilities in institutional rehabilitation face a range of challenges, many of which are closely linked to the duration of their stay in these facilities. Participants expressed feelings of being left behind by societal changes while spending significant portions of their lives within the institution. Other challenges associated with institutional rehabilitation included the loss of social connections, distress stemming from uncertainty about familial care and love and a pervasive sense of abandonment by relatives. In addition, the study highlighted that orphans with intellectual disabilities face heightened vulnerabilities due to early abandonment, inconsistent care environments and systemic barriers. The study recommends the development of individualised transition plans, the eradication of systemic barriers, and the implementation of awareness campaigns to educate and shift societal perceptions. The study also recommends strengthening family and caregiver support systems, alongside advocacy for accessible healthcare, housing, education and employment services as critical for enhancing the well-being of individuals with intellectual disabilities.